Optimization of Improving Organizational Citizenship Behaviour (OCB) through Personality Strengthening, Interpersonal Communication, and Organizational Justice - Andi Hermawan; Eni Susanti (Indonesian Journal of Education and Mathematical Science, 2022)
In educational institutions, teachers are a core part of the management element. Teachers who successfully carry out their main tasks and have the awareness to do something extra will be the key to the success of the organization. Extra activities carried out by teachers that are not directly related to the provisions regarding payroll are called OCB (Organizational Citizenship Behavior). Based on preliminary research, it was found that teachers at SMK PGRI Bogor Regency had relatively low OCB. Therefore, research was needed to obtain good information about other variables that were possibly used to increase OCB. The purpose of this study is to improve teacher OCB by conducting research on the relationship between personality, interpersonal communication, and organizational justice. This study used correlational statistical analysis methods to determine the relationship between the variables studied and the SITOREM method for indicator analysis in order to obtain optimal solutions in order to improve teacher OCB. The population of this study were 289 teachers of SMK PGRI in Bogor Regency. From the population, samples were taken using the Slovin formula and a sample of 168 people was obtained. The results of the analysis using the correlation method show that there is a positive relationship between personality and OCB with a correlation coefficient of ry1 = 0.603. It indicated that personality strengthening can increase OCB. There is a positive relationship between interpersonal communication and OCB with a correlation coefficient ry2 = 0,518 which indicated strengthening interpersonal communication can increase OCB. There is a positive relationship between organizational justice and OCB with a correlation coefficient of ry3 = 0.512 meaning that organizational justice can increase OCB. From the SITOREM analysis, the optimal solution is obtained. Of the 23 indicators studied, there are 14 indicators in good condition so these indicators only need to be maintained or developed, and there are 9 indicators that are still weak so they need to be improved. A priority order for their handling complements improvements to indicators that are still weak. Good indicators are supportive behaviour, technical factors, social status, friendliness, self-disclosure, openness to experience, emotional stability, prudence, wisdom, equality, consistency, maintaining ethics, being informative, and self-respect. The indicators that need to be improved in order of priority for handling are as follows: 1) Trust, 2) Openness, 3) Appreciation for inspiration, 4) Needs, 5) Politeness, 6) Virtue, 7) Prudence, 8) Sportsmanship, and 9 ) Altruism.